The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/cen.13507
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and calcium supplementation, skeletal muscle strength and serum testosterone in young healthy adult males: Randomized control trial

Abstract: Six months of cholecalciferol/calcium supplementation had no significant effect on skeletal muscle strength and serum testosterone in young adult males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 39 publications
2
27
2
1
Order By: Relevance
“…However, mean 25(OH)D values were still above 30.0 nmol/L, indicating absence of VDD in noteworthy fraction in summer. The higher mean serum 25(OH)D levels among indoors in the present study in comparison with values of 25.0 nmol/L in the previous studies could be explained by several ways. The realization of the importance of sunshine exposure among urban indoors in improving vitamin D status during the last two decades and/or inadvertent use of vitamin D supplements among indoors might explain their improved vitamin D status.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…However, mean 25(OH)D values were still above 30.0 nmol/L, indicating absence of VDD in noteworthy fraction in summer. The higher mean serum 25(OH)D levels among indoors in the present study in comparison with values of 25.0 nmol/L in the previous studies could be explained by several ways. The realization of the importance of sunshine exposure among urban indoors in improving vitamin D status during the last two decades and/or inadvertent use of vitamin D supplements among indoors might explain their improved vitamin D status.…”
Section: Discussioncontrasting
confidence: 60%
“…Meta‐analysis of studies assessing effect of vitamin D supplementation in apparently healthy subjects has not shown any remarkable effect on various functional outcomes . In fact, two randomized control trials from our centre showed no significant improvement in muscle strength despite significantly improved vitamin D status after six months of cholecalciferol supplementation . In this context, the present study does not show any functional impact of low serum 25(OH)D among indoors other than borderline raised serum PTH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D supplements appear to improve muscle strength, more so in patients in institutions and with baseline 25(OH)D levels below 30 nmol/L, but high dose supplementation may be deleterious . Confirming the lack of effect of vitamin D on muscle function, even in situations of moderate deficiency, recent studies in young men and women with baseline 25(OH)D levels of about 20 nmol/L have not shown any effects on muscle strength after supplementation to about 75 nmol/L …”
Section: Non‐skeletal Effectsmentioning
confidence: 99%
“…exclusion criteria of the participants (not all vascular ED), the cardiovascular effects of vitamin D are not proper to be regarded as the sole causative factor. Furthermore, several studies have also observed a possible relationship between serum testosterone levels and vitamin D levels(Chin, Ima-Nirwana, & Wan Ngah, 2015;Wang et al, 2015) that had a concordant seasonal variation(Saha et al, 2018). Vitamin D receptor is also present in the testis (Blomberg Jensen et al, 2010), pituitary gland and hypothalamus (Saha et al, 2018), while vitamin D receptor gene knockout mice developed hypergonadotropic hypogonadism(Kinuta et al, 2000).…”
mentioning
confidence: 99%